Au-loaded alkali metal-modified crystalline carbon nitride for photocatalytic nitrogen fixation - Luo, Mimi; Wang, Baibing; Shao, Jiahui; Yan, Yupeng; Jiang, Guanjie; Zhang, Qin; Li, Yang (Carbon Letters, 2024)
Crystalline heptazine carbon nitride (HCN) is an ideal photocatalyst for photocatalytic ammonia synthesis. However, the limited response to visible light has hindered its further development. As a noble metal, Au nanoparticles (NPs) can enhance the light absorption capability of photocatalysts by the surface plasmon resonance (SPR) effect. Therefore, a series of Au NPs-loaded crystalline carbon nitride materials (AH) were prepared for photocatalytic nitrogen fixation. The results showed that the AH displayed significantly improved light absorption and decreased recombination rate of photo-generated carriers owing to the introduction of Au NPs. The optimal 2AH (loaded with 2 wt% Au) sample demonstrated the best photocatalytic performance for ammonia production with a yield of 70.3 μmol g −1 h −1 , which outperformed that of HCN. This can be attributed to the SPR effect of Au NPs and alkali metal of HCN structure. These findings provide a theoretical basis for studying noble metal-enhanced photocatalytic activity for nitrogen fixation and offer new insights into advances in efficient photocatalysts.